Impact of Corporate Governance on Dividend Policy: Study on Publicly Listed Companies on IDX During 2016-2017 - Jessica Jessica (iBuss Management, 2019)
The Indonesian government expects more investors in light of the country’s rapid economic development. In return for their investment, investors gain a right to dividends. To ensure firm management protects shareholders’ rights, companies are expected to have a system called corporate governance. Consequently, in this study, the researcher aims to know the impact of corporate governance on the dividend policy of Indonesian firms. Firm growth, size, profitability, and leverage are also used as independent control variables. Data of 128 companies listed in IDX that consistently distributed dividends during 2016-2017 was collected from the Bloomberg terminal and published annual reports, and analyzed using SPSS and Stata. Multiple Linear Regression results revealed corporate governance has no significant impact on dividend policy; which may be attributed to the changing standards of corporate governance, as well as its lagging effect. Leverage is also found to be insignificant in predicting the dividend policy. Meanwhile, firm size, growth, and profitability are individually found to have a significant positive impact on dividend policy. Keywords:Corporate Governance, Dividend Policy, GCG